PENGARUH FEAR OF MISSING OUT TERHADAP PERILAKU IMPULSIVE BUYING SKINCARE MELALUI ONLINE SHOP PADA MAHASISWI PSIKOLOGI FIPP UNIMA - Raphaela Relcy; Meisie Lenni Mangantes; Sinta E. J. Kaunang (STKIP Subang, 2026)
The rapid growth of social media and e-commerce platforms has significantly influenced consumer behavior, particularly among university students who are active users of digital technology. Continuous exposure to trends and information through social media may trigger Fear of Missing Out (FoMO), a psychological condition characterized by the fear of missing experiences, information, or activities enjoyed by others. This condition is believed to encourage impulsive buying behavior, especially in purchasing skincare products through online shopping platforms. This study aims to examine the influence of Fear of Missing Out (FoMO) on impulsive buying behavior of skincare products through online shops among female students of the Psychology Study Program, Faculty of Education and Psychology, Manado State University. The study employed a quantitative approach with an associative research design. A total of 226 respondents were selected using purposive sampling techniques. Data were collected using a FoMO scale based on the dimensions of competence, autonomy, and relatedness proposed by Przybylski et al. (2013), and an impulsive buying scale based on the cognitive and affective dimensions developed by Verplanken and Herabadi (2001). Data were analyzed using simple linear regression with IBM SPSS Statistics 25. The findings are expected to provide insights into the influence of FoMO on impulsive buying behavior of skincare products among female university students and contribute to the development of consumer psychology studies in the digital era.